Eficácia in vivo de formulações lipossomais de circulação prolongada contendo miltefosina na presença ou ausência de antimoniato de meglumina para o tratamento da leishmaniose visceral - Faria, Karen Ferraz (2016)
Leishmaniases are neglected diseases caused by protozoa Leishmania spp. The main clinic manifestations are cutaneous (LC) and visceral leishmaniasis (LV). LV is able to kill if it is not treated. The treatment in infected patients is still the main step of control of the disease, with several limitations like side effects and reduced effectiveness. For this reason the World Health Organization encourages the search for new drugs or formulations that can minimize these limitations. The aim of this study were prepare, characterized and estimate the effectiveness, in vitro and in vivo, of long-acting liposomal formulations that contains miltefosine in the presence or absence of meglumine antimoniate (AM), for treatment of visceral leishmaniasis. HePC-PEG showed CC50, determined by colorimetric MTT assay in murine macrophages, equal to 97,73μg / mL and HepC-PEG / AM equals 105,06μg / mL, both higher rates than the free miltefosine (44,29μg / mL) suggesting less cellular toxicity of the drug in liposomal formulation. The IC50 values determined by colorimetric assay Resazurin reduction of promastigote forms of Leishmania infantum are similar to HePC-PEG (30,72μg / ml), PEG-HEPC / AM (32,65μg / ml) and free miltefosine (34.23 mg / mL), suggesting that there was no reduction in the leishmanicidal activity of miltefosine in the formulations. Against intracellular amastigotes, the pegylated formulations significantly reduced macrophages infection rates compared to the control and treated macrophages AM and LAM. There was no change in renal function in acute toxicity tests and therapeutic efficacy. However, the enzymes used to evaluate liver function test were increased therapeutic efficacy of the HePC-PEG treated groups, HEPC-PEG/AM free and miltefosine. The biodistribution test indicate higher concentrations of Sb in the blood of BALB/c animals treated with HEPC-PEG/AM in the HEPC-PEG + LAM group throughout kinetics 96h, In the liver 96 hours after the treatment the concentration of Sb is greater in the HEPC-PEG + LAM group in HEPC-PEG/AM. These results suggest the influence of the lipid composition in the Sb biodistribution. Animals treated with the HePC-PEG/AM formulations HePC-PEG + AM and miltefosine showed a significant reduction of the parasite load in the liver and spleen compared to control group. The HePCPEG/AM formulation was the one with the best results in suppression of the parasitic load of the mice, with significant reduction in the number of parasites in relation to control groups and AM in the liver and in the control, AM, LAM and HePCPEG spleen . Similarly, the mixture HEPC-PEG + LAM reduced parasitic load significantly in the liver compared to the control group and in the spleen compared to control groups and AM, while the free miltefosine reduced parasitic load only in the control group. First proof of concept that the innovative formulations HePC-PEG / AM and HePC-PEG + LAM nanosystems have characteristics of stable, monodisperse, biocompatible and induce significant reduction of L. infantum infection rates in vitro and in live, was confirmed. These results reinforce the therapeutic potential of these formulations and open new perspectives for the treatment of VL